The Definitive Guide to MongoDB The NoSQL Database for Cloud and Desktop Computing - Plugge, Eelco; Membrey, Peter; Hawkins, Tim.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
MongoDB, a cross-platform NoSQL database, is the fastest-growing new database in the world. MongoDB provides a rich document-oriented structure with dynamic queries that you$1 (Bll recognize from RDBMS offerings such as MySQL. In other words, this is a book about a NoSQL database that does not require the SQL crowd to re-learn how the database world works! MongoDB has reached 1.0 and boasts 50,000+ users. The community is strong and vibrant and MongoDB is improving at a fast rate. With scalable and fast databases becoming critical for today$1 (Bs applications, this book shows you how to install, administer and program MongoDB without pretending SQL never existed.s
Basics -- to MongoDB -- Installing MongoDB -- The Data Model -- Working with Data -- GridFS -- Developing -- PHP and MongoDB -- Python and MongoDB -- Creating a Blog Application with the PHP Driver -- Advanced -- Database Administration -- Optimization -- Replication -- Sharding.
Keywords: Computer science; Database management; Computer Science; Database Management